ROJENA V NAREČJE. AKADEMIKINJI PROF. DR. ZINKI ZORKO OB 80-LETNICI. Uredil Marko Jesenšek: Maribor: Filozofska fakulteta, Mednarodna založba Oddelka za slovanske jezike in književnosti, 2015. (Mednarodna knjižna zbirka Zora, 114). 727 str. - Krajnc Ivič, Mira; Zemljak Jontes, Melita (Slavia Centralis, 2020)
The article presents the monograph Rojena v narečje (Born in Dialect), which is dedicated to the 80th anniversary of the academician and professor emeritus of the Department of Slavic Languages ​​and Literature at the Faculty of Arts, University of Maribor, dr. Zinka Zorko.